Beyond Canon: How X Platform's AU Fanfiction Engagement Influences Filipino Gen Z Self-Concept and Well-being - Aguilar, Chelsea Dominique C.; Berana, Xzareena Christianne L.; Declaro, Maria Kaeysha I.; Arcinas, Myla M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Fanfiction has emerged as a significant digital reading and storytelling platform, particularly Alternate Universe (AU) fanfiction on X. This study examined the relationship between AU fanfiction engagement, self-concept, and well-being among Filipino Gen Z readers. Using a quantitative-correlational design, data were collected from 150 participants aged 18-27 (M =Enga 21.3, SD = 2.4) through an online survey. Respondents were selected using purposive non-probability sampling to identify active fanfiction community members. Standardized instruments included the Reading Flow Short Scale, Tennessee Self-Concept Scale, and BBC Well-Being Scale. Descriptive and inferential statistics were applied to analyze the data. Findings revealed high engagement with AU fanfiction, particularly in time spent and emotional immersion (Mdn = 5.5, IQR = 1.2). Self-concept scores were strongest in moral (Mdn = 4.25, IQR = 0.75) and social dimensions (Mdn = 4.0, IQR = 0.83), while personal self-concept, including self-satisfaction and confidence, were comparatively lower (Mdn = 3.2, IQR = 1.1). Well-being assessment highlighted strengths in social (Mdn = 3.83, IQR = 0.92) and psychological aspects (Mdn = 3.88, IQR = 0.76) but weaknesses in physical health (Mdn = 3.25, IQR = 1.05), particularly sleep quality. The Spearman Rho correlation results indicated minimal direct relationships between fanfiction engagement and self-concept (r = 0.053, p = .519, 95% CI [-0.107, 0.211]) and well-being (r = -0.038, p = .644, 95% CI [-0.197, 0.123]), suggesting that engagement alone does not significantly shape these aspects. Regression analysis further supported these findings, showing a minimal positive impact on self-concept (β = 0.039) and a minimal negative impact on well-being (β = -0.038). These results highlight the complexity of fanfiction's influence on self-concept and well-being, demonstrating the need for more nuanced research examining potential mediating and moderating variables within this relationship.